2018
DOI: 10.1016/j.apcatb.2017.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical CO2 recycling via dry and bi reforming of methane using Ni-Sn/Al2O3 and Ni-Sn/CeO2-Al2O3 catalysts

Abstract: Carbon formation and sintering remain the main culprits regarding catalyst deactivation in the dry and bi-reforming of methane reactions (DRM and BRM, respectively). Nickel based catalysts (10 wt.%) supported on alumina (Al2O3) have shown no exception in this study, but can be improved by the addition of tin and ceria. The effect of two different Sn loadings on this base have been examined for the DRM reaction over 20 h, before selecting the most appropriate Sn/Ni ratio and promoting the alumina base with 20 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
111
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 41 publications
11
111
0
Order By: Relevance
“…For the Ce-containing catalyst, the addition of CeO 2 gives a broad reduction peak around 250°C due to the Ni-Ce interaction. As previously reported elsewhere, the presence of ceria improves Ni reducibility at lower temperatures and the overall redox properties of all the studied catalysts due to its excellent oxygen mobility [34]. Furthermore, a distinctive peak at a higher temperature (875°C) can be observed on the profiles of Ni/CeAl, NiCr/CeAl and NiFe/CeAl, which is associated to the reduction of bulk ceria [34].…”
Section: Reducibility: H 2 -Tprsupporting
confidence: 51%
“…For the Ce-containing catalyst, the addition of CeO 2 gives a broad reduction peak around 250°C due to the Ni-Ce interaction. As previously reported elsewhere, the presence of ceria improves Ni reducibility at lower temperatures and the overall redox properties of all the studied catalysts due to its excellent oxygen mobility [34]. Furthermore, a distinctive peak at a higher temperature (875°C) can be observed on the profiles of Ni/CeAl, NiCr/CeAl and NiFe/CeAl, which is associated to the reduction of bulk ceria [34].…”
Section: Reducibility: H 2 -Tprsupporting
confidence: 51%
“…The surface of nickel catalyst incorporating basic metal oxide is favored by CO 2 adsorption, leading to the increase in CO 2 adsorption that can enhance its reaction with carbon and thus inhibits carbon deposition. The addition of a second metal, such as Co, Cu, and Sn, can form less C‐sensitive alloys . Choi et al.…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
“…demonstrated that a partial coverage of the nickel surface of Ni/Al 2 O 3 by MnO X promoted the adsorption of CO 2 , leading to the decrease in the carbon deposition . Ni/Al 2 O 3 catalyst can also be improved by tin and ceria, leading to enhanced conversion and stability . Noble metals (such as Pt, Ru, and Pd) can remarkably enhance both activity and stability due to their excellent ability to maintain Ni reduced .…”
Section: Dry Reforming Of Methanementioning
confidence: 99%
See 1 more Smart Citation
“…These processes are usually conducted by exposing the catalysts to certain atmosphere for some time at some prescribed temperatures. Ni catalysts are probably among the most commonly used due to their effectiveness and low costs, they are versatile and have been used in numerous reactions . One of the reactions is dry reforming of methane (DRM), in which two greenhouse gases (CH 4 and CO 2 ) are converted to valuable syngas (H 2 and CO) .…”
Section: Introductionmentioning
confidence: 99%